Introduction to Annotated Logics Foundations for Paracomplete and Paraconsistent Reasoning Introduction - Abe, Jair Minoro [UNESP]; Akama, Seiki; Nakamatsu, Kazumi; Abe, JM; Akama, S; Nakamatsu, K (Springer, 2015)
This chapter gives motivations and the history of annotated logics as an introduction to this book. First, we discuss the importance of annotated logics in connection with paraconsistent logics. Second, we present the history of annotated logics by reviewing the literature on the subject.